New liquid supports for the immobilisation of laccase and production of polydopamine - Pereira, Ana Filipa S. (2021)
Based on the principles of green chemistry, enzymatic biocatalysis contributes to a more eco-friendly and sustainable industrial chemistry [1]. Therefore, its wide use in industrial and biotechnological processes has increasingly become more evident [1]. One promising application is the enzymatic polymerization of various compounds. Laccase, a multicopper oxidase with high catalytic efficiency and low substrate specificity, has attracted worldwide attention due to its ability to degrade both phenolic and non-phenolic compounds and its involvement in polymer synthesis [2]. Being accepted as an environmentally friendly biocatalyst, laccase is widely employed in the most sectors of biotechnology [2]. Polydopamine (PDA), an added-value biopolymer that results from the dopamine polymerization, has been used for many applications, being highlighted the modification and functionalization of surfaces and in the field of biomedicine [3]. In contrast to the conventional method of dopamine polymerization, which is a time-consuming process and produces PDA films with poor stability, in the presence of laccase the process becomes faster, very efficient and meets the ideals of green chemistry [4]. However, applying a biocatalyst that could be reused and without the loss of its biological properties is an ever-increasing demand for its industrial applications [5]. Thereby, ionic-liquid-based aqueous biphasic systems (IL-based ABS), which are mainly composed of water, appear as a promising alternative in this field since they provide a mild and biocompatible environment for proteins [6]. Besides, these systems efficiently allow the separation of the product of interest and the reusability of the enzyme in an unique step [7]. In this study it was carried out the polymerization of dopamine by using laccase as the biocatalyst. Several parameters including the ideal temperature, medium pH and different initial dopamine concentrations on the polymerization rate have been investigated and optimized. Besides, to develop an integrated and sustainable platform for the production of PDA, that allow the reusability of the enzyme and the separation of this product, different ABS composed of polymers, salts and ionic liquids have been used.